STUDI KELAYAKAN SOFTWARE SISTEM PAKAR METODE FORWARD CHAINING DALAM MENDETEKSI KARIES GIGI - Ani Subekti; Subinarto Subinarto; Sariyem Sariyem (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2016)
The purpose to design expert system software to facilitate users in getting the diagnosis and treatment advice in accordance with the symptoms of caries. Disease diagnosis expert system software dental caries forward chaining method has been designed and is necessary to do a feasibility study. The purpose of this study was to determine the feasibility study software in diagnosing dental caries. This research is a quantitative description of the cross-sectional approach. The feasibility study aims to determine whether the software software is acceptable or not as the media detection of dental caries disease. The feasibility study using 20 patients software dental caries, five IT specialists and 10 dentists in Semarang. Data from the feasibility study displayed a frequency distribution. In the aspect of feasibility software technology gives patients by 95% In the operational aspects of IT specialists, dentists and patients give the feasibility on top of ≥ 75%. By feasibility law gives patients the feasibility of 90%, results showed the expert system software forward chaining method 100% deserved by all three groups of respondents, dentists, IT and software users. This expert system software are suggested for the validation test to be used in detecting correctly between diagnosis dentist with the results of diagnostic software.